A security architecture for medical application platforms - Salazar, Carlos (Kansas State University, 2014)
The Medical Device Coordination Framework (MDCF) is an open source Medical Application Platform (MAP) that facilitates interoperability between heterogeneous medical devices. The MDCF is designed to be an open test bed for the conceptual architecture described by the Integrated Clinical Environment (ICE) interoperability standard. In contrast to existing medical device connectivity features that only provide data logging and display capabilities, a MAP such as the MDCF also allows medical devices to be controlled by apps. MAPs are predicted to enable many improvements to health care, however they also create new risks to patient safety and privacy that need to be addressed. As a result, MAPs such as the MDCF and other ICE-like systems require the integration of security features. This thesis lays the groundwork for a comprehensive security architecture within the MDCF. Specifically, we address the need for access control, device certification, communication security, and device authentication. We begin by describing a system for ensuring the trustworthiness of medical devices connecting to the MDCF. To demonstrate trustworthiness of a device, we use a chain of cryptographic certificates which uniquely identify that device and may also serve as non- forgeable proof of regulatory approval, safety testing, or compliance testing. Next, we cover the creation and integration of a pluggable, flexible authentication system into the MDCF, and evaluate the performance of proof-of-concept device authentication providers. We also discuss the design and implementation of a communication security system in the MDCF, which enables the creation and use of communication security providers which can provide data confidentiality, integrity, and authenticity. We conclude this work by presenting the requirements and a high level design for a Role-Based Access Control (RBAC) system within the MDCF.
Keywords: Medical device coordination; Computer security; Security architecture; Integrated clinical environment; Medical application platform; Computer Science (0984)